SOCIO-ECONOMIC AND CULTURAL IMPACTS OF TOURISM IN BANGLADESH - Lincoln, Zakaria (European Scientific Journal, ESJ, 2014)
The current research article analyzed socio-economic and cultural impact of tourism in Bangladesh. It has discussed in-bound tourists; their purpose of visit; economic contribution; growth and contribution to employment. The study ended with a discussion on negative affects of tourism on society and culture in Bangladesh.